Diagnostic value of biochemical markers of bone metabolism in treatment of generalized periodontitis in patients with age-related osteoporosis - O. O. Fastovets; I. V. Masheiko; H. B. Peleshenko (Regulatory Mechanisms in Biosystems, 2018)
The topicality of the problem of periodontal diseases is due to their significant prevalence. The purpose of this work is to study the dynamics of markers of bone metabolism in the process of treatment of generalized periodontitis of the II–III levels of severity in patients with age-related osteoporosis and without osteoporotic changes in the skeleton. The examination and treatment of 104 patients, aged 63–78, equal ratio of men and women, was conducted. Among the selected patients, 49 persons had normal bone mineral density, while the remaining 55 had osteoporotic changes in the bone tissue of involutory genesis. All subjects were assessed for the following indicators ; mineral density of jaw bone tissue (BMD) according to the results of the computer tomography, the concentration of C-Propeptide of Type I Procollagen (CICP) in blood plasma, the activity of tartrate-resistant acid phosphatase (TRAP), bone alkaline phosphatase (BAP), osteocalcin, parathyroid hormone in blood serum, concentration of β-CrossLaps in urine, total calcium and inorganic phosphorus content in blood with calculation of the Ca/P index. It was established that in patients with periodontitis of the II–III degree there was a decrease in the BMD of the alveolar bone in comparison with the control values (P ˂ 0.05), whereas the presence of systemic osteopenia worsened the indices (P ˂ 0.001). The least osteoregenerative activity, which was characterized by the decrease in BAP, TRAP and CICP levels, was registered in patients with generalized periodontitis of the III degree on the background of age-related osteoporosis (P ˂ 0.05). In the patients with generalized periodontitis of the III degree of severity, at the beginning of treatment, a weak negative correlation was found between BMD and TRAP activity (r = –0.292, P < 0.05) and mean strength correlation – with β-CrossLaps in urine (r = –0.348, P < 0.01). The concentration of CICP positively correlated with the mineral density of bone tissue from the third month after the start of treatment (r = 0.312, P < 0.05). As a conclusion, the mineral density of alveolar bone in the process of treatment varies unevenly depending on the severity of generalized periodontitis and the character of osteoporotic changes in the skeleton. The biochemical markers of bone metabolism allow the balance of processes of bone resorption and formation to be determined in order to correct treatment of generalized periodontitis.